2020
DOI: 10.15587/1729-4061.2020.214934
|View full text |Cite
|
Sign up to set email alerts
|

Developing an improver of targeted action for the prolonged freshness of bread made from wheat flour

Abstract: 62 dough, the course of the technological process, the quality of bakery products and their shelf life [4]. There is a lot of competition in the market for complex bakery improvers, since their range is very diverse, depending on the direction of their action, different pricing policy and raw material base [5]. Complex bakery improvers consist of a functional base and an active part. Flour, extruded flour, starch, dry wheat gluten and others are used as a functional base. The active part includes gluten oxidiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The accumulation of dextrins in the finished products was investigated according to the procedure given in [25].…”
Section: Methods To Study the Quality Of The Pastry Product Containing The Polycomponent Mixture "Solodok"mentioning
confidence: 99%
“…The accumulation of dextrins in the finished products was investigated according to the procedure given in [25].…”
Section: Methods To Study the Quality Of The Pastry Product Containing The Polycomponent Mixture "Solodok"mentioning
confidence: 99%
“…The National University of Food Technologies (Ukraine) has developed a technology for enrichment of dry milk whey with Mg and Mn [10]. It was found that whey powder enriched with Mg and Mn is a good functional basis in the production of complex bakery improvers [12]. Powdered milk whey enriched with Mg and Mn was selected for the MCM formulation to reduce the activity of enzymes in germinated grains.…”
Section: Introductionmentioning
confidence: 99%